Bleb Plication for a Leaking Bleb After Trabeculectomy. Issue 8 (August 2020) - Sugimoto, Koichiro; Asano-Shimizu, Kimiko; Murata, Hiroshi; Yamashita, Takehiro; Asaoka, Ryo
Abstract : Purpose: The purpose of this work was to report a new method for the repair of ischemic bleb leaks. Bleb leakage is a serious complication of glaucoma filtering surgery with mitomycin C. Many surgical methods have been proposed to seal the leakage from a bleb; however, this novel plication method is effective, relatively easy to perform, and safe. Methods: We describe the case reports of 2 patients with leakage from a bleb who were treated with the new method. The conjunctiva was lifted away from the sclera as extensively as possible around the ischemic conjunctiva toward the fornix using a bleb knife. Thereafter, 10-0 nylon sutures were applied between the nonischemic conjunctiva located just outside the ischemic conjunctiva and the corneal limbus. The ischemic conjunctiva was not removed, but covered with the nonischemic conjunctiva that was advanced toward the corneal limbus by these sutures. Results: After treatment, no recurrence of bleb leakage was observed. Moreover, no ischemic changes were observed in the advanced nonischemic conjunctiva or plicated conjunctiva. Conclusion: This new method of bleb plication was effective for sealing bleb leakage.